2020
DOI: 10.1371/journal.pone.0230952
|View full text |Cite
|
Sign up to set email alerts
|

Using Maize δ15N values to assess soil fertility in fifteenth- and sixteenth-century ad Iroquoian agricultural fields

Abstract: Native Americans developed agronomic practices throughout the Western Hemisphere adapted to regional climate, edaphic conditions, and the extent of dependence on agriculture for subsistence. These included the mounding or "corn hill" system in northeastern North America. Iroquoian language speakers of present-day New York, USA, and Ontario and Qué bec, Canada were among those who used this system. While well-known, there has been little archaeological documentation of the system. As a result, there is scant ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“… Animal foddering: many domesticated animals are fed on a variety of agricultural crop by‐products 94 . This study has shown that all components of the plant are enriched during biofertilisation and not just the human‐consumed part of the plant. There is very strong evidence for fish fertilisation in North America 95 ; therefore, it may be worth considering its impact on ancient farming practices and palaeodiets in this region of the world. During the Medieval period there was increased reliance on the use of marine resources in different areas of the world, such as north‐west Europe 96 and the North Atlantic region 97 . Therefore, biofertilisers such as seaweed and fish (as products of domestic rubbish) may have led to a general increase in δ 15 N and δ 34 S value around agricultural or urban settlements compared with more inland communities.…”
Section: Discussionmentioning
confidence: 96%
“… Animal foddering: many domesticated animals are fed on a variety of agricultural crop by‐products 94 . This study has shown that all components of the plant are enriched during biofertilisation and not just the human‐consumed part of the plant. There is very strong evidence for fish fertilisation in North America 95 ; therefore, it may be worth considering its impact on ancient farming practices and palaeodiets in this region of the world. During the Medieval period there was increased reliance on the use of marine resources in different areas of the world, such as north‐west Europe 96 and the North Atlantic region 97 . Therefore, biofertilisers such as seaweed and fish (as products of domestic rubbish) may have led to a general increase in δ 15 N and δ 34 S value around agricultural or urban settlements compared with more inland communities.…”
Section: Discussionmentioning
confidence: 96%
“…and then offsets from [46] were added to each of the human ratios (S2 Table 1, online). Maize δ 13 C and δ 15 N were taken from [50]. Mann-Whitney and Epps-Singleton statistical tests were done in PAST version 4.11 [51].…”
Section: Discussionmentioning
confidence: 99%
“…To obtain δ 13 C and δ 15 N estimates for human feces, the TEF (5 for δ 13 C, 3 for δ 15 N) was subtracted from and then offsets from 47 were added to each of the human ratios (S2 Table 1 , online). Maize δ 13 C and δ 15 N were taken from 49 . Source means and concentration values are provided in S2 Table 6 , online.…”
Section: Methodsmentioning
confidence: 99%